PEG-fibrinogen hydrogel microspheres as a scaffold for therapeutic delivery of immune cells - Cohen, Noam; Vagima, Yaron; Mouhadeb, Odelia; Toister, Einat; Gutman, Hila; Lazar, Shlomi; Jayson, Avital; Artzy-Schnirman, Arbel; Sznitman, Josué; Ordentlich, Arie; Yitzhaki, Shmuel; Seliktar, Dror; et al. (Frontiers in Bioengineering and Biotechnology, 2022)
Recent advances in the field of cell therapy have proposed new solutions for tissue repair and regeneration using various cell delivery approaches. Here we studied ex vivo a novel topical delivery system of encapsulated cells in hybrid polyethylene glycol-fibrinogen (PEG-Fb) hydrogel microspheres to respiratory tract models. We investigated basic parameters of cell encapsulation, delivery and release in conditions of inflamed and damaged lungs of bacterial-infected mice. The establishment of each step in the study was essential for the proof of concept. We demonstrated co-encapsulation of alveolar macrophages and epithelial cells that were highly viable and equally distributed inside the microspheres. We found that encapsulated macrophages exposed to bacterial endotoxin (LPS) preserved high viability and secreted moderate levels of TNFα, whereas non-encapsulated cells exhibited a burst TNFα secretion and reduced viability. LPS-exposed encapsulated macrophages exhibited elongated morphology and out-migration capability from microspheres. Microsphere degradation and cell release in inflamed lung environment was studied ex vivo by the incubation of encapsulated macrophages with lung extracts derived from intranasally infected mice with Yersinia pestis, demonstrating the potential in cell targeting and release in inflamed lungs. Finally, we demonstrated microsphere delivery to a multi-component airways-on-chip platform that mimic human nasal, bronchial and alveolar airways in serially connected compartments. This study demonstrates the feasibility in using hydrogel microspheres as an effective method for topical cell delivery to the lungs in the context of pulmonary damage and the need for tissue repair.